Left Atrial Function in Different Modes of Heart-Rate Lowering Therapy with Beta-Blockers in Patients with Recurrent Atrial Fibrillation and Hypertension - E. V. Kokhan; G. K. Kiyakbaev; E. M. Ozova; V. A. Romanova; Zh. D. Kobalava (Столичная издательская компания, 2021)
Aim. To study the impact of heart rate (HR) reduction with beta-blockers (BB) on left atrial (LA) function in hypertensive patients with paroxysmal or persistent mild symptomatic atrial fibrillation.Material and methods. In this open prospective trial we randomly assigned patients with hypertension, sinus rhythm, elevated heart rate (≥70 bpm), and recurrent atrial fibrillation (EHRA 2A or less) to receive BB with a target HR of less or greater than 70 bpm for at least 4 months. All the patients underwent an echocardiogram [left atrial (LA) function was assessed as emptying fraction]and applanation tonometry at baseline and after 4 months. Primary endpoint was median LA emptying fraction (LAEF) measurement at the end of the study.Results. 47 patients were randomized to group with a target HR of ≤70 bpm and 44 patients to >70 bmp. Among them 44 and 41 patients completed the study. Median follow up was 4.4 months. At the end of the study (4.5 months) median HR was 62 [60; 67] bmp in ≤70 group and 73 [72; 76] bpm in >70 group. Both groups received similar antihypertensive therapy and there were no intergroup differences in systolic and diastolic blood pressure. At the end of the study, patients in ≤70 group had significantly lower LAEF compared with >70 group (37% vs 42%; p=0.01). E'avg was lower and augmentation index was higher in ≤70 group as compared to >70. In regression analysis, after E'avg and augmentation index were included in the model, the association between LAEF and randomization group lost its significance.Conclusion. Beta blockers treatment with strict HR reduction (≤70 bpm) significantly reduced LA function as compared to lenient target HR (>70 bpm).